Abnormal Dynamic Functional Networks in Subjective Cognitive Decline and Alzheimer's Disease - Wang, Jue; Wang, Kexin; Liu, Tiantian; Wang, Li; Suo, Dingjie; Xie, Yunyan; Funahashi, Shintaro; Wu, Jinglong; Pei, Guangying (Frontiers in Computational Neuroscience, 2022)
Subjective cognitive decline (SCD) is considered to be the preclinical stage of Alzheimer’s disease (AD) and has the potential for the early diagnosis and intervention of AD. It was implicated that CSF-tau which increases very early in the disease process in AD has a high sensitivity and specificity to differentiate AD from normal aging, and the highly connected brain regions behaved more tau burden in AD patients. Thus, a highly connected state measured by dynamic functional connectivity may serve as the early changes of AD. In this study, forty-five normal controls (NC), thirty-six individuals with SCD and thirty-five AD patients were enrolled to obtain the resting-state functional magnetic resonance imaging scanning. Sliding windows, Pearson correlation and clustering analysis were combined to investigate the different levels of information transformation states. Three states, including the low state, middle state and high state were characterized based on the strength of functional connectivity between each pair of brain regions. For the global dynamic functional connectivity analysis, statistically significant differences were found among groups in the three states and the functional connectivity in middle state was positively correlated to cognitive scales. Furthermore, the whole brain was parcellated into four networks, including default mode network (DMN), cognitive control network (CCN), sensori-motor network (SMN) and occipital-cerebellum network (OCN). For the local network analysis, statistically significant differences in CCN for low state, SMN for middle state and high state, were found in normal controls and AD patients. Meanwhile, the differences were also found in normal controls and individuals with SCD. In addition, the functional connectivity in SMN for high state was positively correlated to cognitive scales. Converging results showed the changes of dynamic functional states in individuals with SCD and AD patients. And the changes were mainly in the high strength of functional connectivity state.